Portugal : Second Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report, 2011)
Portugal's economic adjustment has continued, but the contraction in output has been milder than expected. The 2012 outlook for Europe has deteriorated substantially, with growth revised down by 1u percentage points relative to spring forecasts. Substantially higher capital requirements across Europe, coupled with cuts in exposure to the periphery, are placing further pressure on banks and the flow of credit. The authorities have made significant progress in revenue administration reform and public administration restructuring.